Experimental Investigation of Sloshing in the Rectangular Tank Under the Hydrophobic Effect - Korkmaz, Fatih Cuneyd; Yigit, Kenan; Guzel, Bulent (IOS PRESS, 2018)
Liquid sloshing causes ship tank's surface to be damaged. In this study, this phenomenon was analyzed experimentally in rectangular tank model. Partially filled tank has been experienced and it was excited at single frequency range by direction of sway. Experiments were carried out with uncoated and hydrophobic coated tank. Only one water level was chosen for demonstrate sloshing effects on the different tank surface parameters. Wave path, wave breaking and shape of wave during flip-through were cough by high speed camera images. Strain gages have also been implemented to lateral side of tank to show local reaction of structure by measuring liquid induce deformation. Besides that, all experiments have been repeated by changed surface parameters at two contrast lateral sides on tanks. The surface parameter has been modified by applying hydrophobic coat. The coated surfaces propose to increase degrees of the contact angle between water drop and structure surface. The comparisons have been conducted within considering the images and measured results in coated, non-coated surface at tank sloshing experiments. The results show that the hydrophobic surface decreased the sloshing force on lateral sides, wave propagated more splay and water couldn't reach the level of wave as non-coated surface.
Keywords: Ship tank; sloshing; hydrophobic; IMPACT; Engineering